Uji Aktivitas Antiproliferasi Formula Liposom Ekstrak Etanol Kunyit (Curcuma domestica) Terhadap Sel Kanker Payudara T47D - Pasaribu, Gabriella; Iskandarsyah, Iskandarsyah; Sagita, Erny (Pharmaceutical Sciences and Research, 2016)
Breast cancer is one of deadliest diseases in world. Turmeric extract was known to have antiproliferative activity. To minimize its toxicity, turmeric extract was encapsulated with liposome, a vesicle lipid bilayer functioned as cancer drug carrier in body. This research aimed to determine encapsulation effect of turmeric ethanol extract against antiproliferative activity in T47D breast cancer cells through in vitro assay. Liposomes was made using thin layer method and particle size was reduced by extrusion. Materials used are phosphatidylcholine, cholesterol, and turmeric extract. Optimization of liposomes was made in three formulations with different concentrations of extract. Most optimal formulation was formulation with minimum amount of extract, judging from physical parameters which have smallest precipitates and longest settling time. Evaluation liposome particle size and zeta potential was used DLS, morphology was used TEM, and entrapment efficiency was used dialysis. Most optimal formulation was tested their antiproliferative activity compared with not encapsulated extracts used 3-(4,5-dimethylazole-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. There was decrease antiproliferative activity of encapsulated extracts. IC50 encapsulated extracts was 45.762 μg/ml and IC50 extracts was 36.399 μg/ml. Liposome particle size was below 445 nm. Zeta potential was -7.51 mV. Morphology was LUV and MVV. Entrapment efficiency was 63.80%. It could be concluded that encapsulation of turmeric extract into liposome could reduce its toxicity against cancer cells.